1998
DOI: 10.1093/jnci/90.13.972
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing Second Primary Tumors From Lung Metastases in Patients With Head and Neck Sauamous Cell Carcinoma

Abstract: In patients with HNSCC and a solitary SCC in the lung, microsatellite analysis provides a rapid genetic approach for discerning clonal relationships. In such patients, we found that a solitary SCC in the lung more likely represents a metastasis than an independent lung cancer. Microsatellite analysis could potentially be applied to any patient with multiple tumors, where tumor relationships are not clear on clinical, radiographic, or even histopathologic grounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
93
0
5

Year Published

2001
2001
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 163 publications
(102 citation statements)
references
References 18 publications
4
93
0
5
Order By: Relevance
“…Hence, extrapolation of our validation data to all tumor pairs, including those that are TP53 wild-type, should be done with caution, and this is also a reason that our algorithm for interpretation of LOH results allows some discordant LOH. It has been suggested that in multiple chromosomes, breakpoints should be relied upon instead of LOH patterns (16). However, in our previous study, we showed that even breakpoint analyses might lead to misinterpretations, particularly when TP53 is wild-type (12).…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Hence, extrapolation of our validation data to all tumor pairs, including those that are TP53 wild-type, should be done with caution, and this is also a reason that our algorithm for interpretation of LOH results allows some discordant LOH. It has been suggested that in multiple chromosomes, breakpoints should be relied upon instead of LOH patterns (16). However, in our previous study, we showed that even breakpoint analyses might lead to misinterpretations, particularly when TP53 is wild-type (12).…”
Section: Discussionmentioning
confidence: 71%
“…We further evaluated whether immunohistochemical analysis of p53 expression in the SCC of both the head and neck and lung could be of help, at least as an initial quick screen. Positive immunostaining for p53 is presumptive evidence for gene mutation, as more than 90% of missense mutations will result in abnormal p53 protein accumulation (16). Immunohistochemistry is a simple and fast technique, and easily implemented at any pathology laboratory.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we used microsatellite markers on 11 different chromosome arms, whereas others analyzed multiple markers on two to six chromosome arms (6,10,27,28). In general, clonality was decided on the basis of concordant LOH of at least two loci, whereas in some articles the additional criterion of identical p53 mutations was used, if present (6,10,27,28).…”
Section: Discussionmentioning
confidence: 99%
“…In general, clonality was decided on the basis of concordant LOH of at least two loci, whereas in some articles the additional criterion of identical p53 mutations was used, if present (6,10,27,28). This approach, however, overlooks the phenomenon that LOH on different loci is not an independent process as we and others (17) have shown.…”
Section: Discussionmentioning
confidence: 99%